Strain improvement of Chlorella sp. for phenol biodegradation by adaptive laboratory evolution. (April 2016) - Wang, Libo; Xue, Chuizhao; Wang, Liang; Zhao, Quanyu; Wei, Wei; Sun, Yuhan
Graphical abstract: Highlights: Adaptive evolution was performed for Chlorella sp. to remove phenol in wastewater. The resulting strain was obtained after 31 cycles for about 95 d. The resulting strain could grow under 500 mg/L and 700 mg/L phenol. The growth rates of resulting strain were more than twice of those of original one. 500 mg/L phenol could be fully removed in 7 d by the resulting strain. Abstract: Microalgae are highly efficient photosynthesis cell factories for CO2 capture, biofuel productions and wastewater treatment. Phenol is a typical environmental contaminant. Microalgae normally have a low tolerance for, and a low degradation rate to, high concentration of phenol. Adaptive laboratory evolution was performed for phenolic wastewater treatment by Chlorella sp. The resulting strain was obtained after 31 cycles (about 95 d) under 500 mg/L phenol as environmental stress. It could grow under 500 mg/L and 700 mg/L phenol without significant inhibition. The maximal biomass concentrations of the resulting strain at day 8 were 3.40 g/L under 500 mg/L phenol and 2.70 g/L under 700 mg/L phenol, respectively. They were more than two times of those of the original strain. In addition, 500 mg/L phenol was fully removed by the resulting strain in 7 d when the initial cell density was 0.6 g/L.